Size matters: Influence of center size on quality of diabetes control in children and adolescents with type 1 diabetes—A longitudinal analysis of the DPV cohort. Issue 1 (23rd November 2021) - Hackl, Lukas; Bonfig, Walter; Bechtold‐Dalla Pozza, Susanne; Lanzinger, Stefanie; Treptau, Nicole; Raile, Klemens; Elpel, Ulf; Ludwig, Karl‐Heinz; Buchal, Gebhard; Holl, Reinhard W.
Abstract: Background: Treatment of patients with type 1 diabetes requires experience and a specific infrastructure. Therefore, center size might influence outcome in diabetes treatment. Objective: To analyze the influence of center size on the quality of diabetes treatment in children and adolescents in Germany and Austria. Patients and methods: In 2009 and 2018, we analyzed metabolic control, acute complications, and rates of recommended screening tests in the DPV cohort. Diabetes centers were classified according to the number of patients from "XS" to "XL" (<20 [XS], ≥20 to <50 [S], ≥50 to <100 [M], ≥100 to <200 [L], ≥200 [XL]). Results: Over the 10‐year period, metabolic control improved significantly in "M", "L" and "XL" diabetes centers. Treatment targets are best achieved in "M" centers, while "XS" centers have the highest mean hemoglobin A1c. The relation between hemoglobin A1c and center size follows a "v‐shaped" curve. In 2009, conventional insulin therapy was most frequently used in "XS" centers, but in 2018, there was no difference in mode of insulin therapy according to center size. Use of CSII and sensor augmented CSII/hybrid closed loop increased with center size. Patients cared for in "XS" diabetes centers had the fewest follow‐up visits per year. The rates of severe hypoglycemia and DKA were lowest in "XL" diabetes centers, and the rate of DKA was highest in "XS" centers. Conclusion: Center size influences quality of care in pediatric patients with type 1 diabetes. Further investigations regarding contributing factors such as staffing and financial resources are required.